ANALISIS SWOT TERHADAP PASAR INDUK SELIDAH HANDIL BAKTI KECAMATAN ALALAK KABUPATEN BARITO KUALA PROVINSI KALIMANTAN SELATAN - Sarifah Nur Isra Jairina; Deasy Arisanty; Karunia Puji Hastuti (JPG (Jurnal Pendidikan Geografi), 2015)
Central market is a economi means to provided easly for a society to do transaction buying and selling an item. The item at central market ussually to selling too at markets or a smaller place. The items that sold at central that is of crude items (basic) like agricultural product and plantation, half-cooked item until finished item. Selidah’s central market handil bakti is a central market wich to located at sub-district of alalak barito kuala regency south Kalimantan province. Selidah’s central market handil bakti happened various activity buying and selling between marketeer dan buyer, but the items sold in the central market, it too much only crude items and operating every week. Selidah’s central market has many problems to meet the everyday neededs in transaction buying and selling of items,it can be analyzed internal aspects (stronger and weaker)and eksternal (opportunities and threats) with SWOT analysis. The result can be seen of weight total from each factor that is total score for power factor is 1.26, total score for weakness factor is 1.03, total score for opportunities factor is 2.28, and total score for threat factor is 0.68. selidah’s central market handil bakti standed at quadrant I with the coordinate point (0.11 : 0.8) used SWOT matriks.  Keywords: central market, SWOT analysis